Effects of a short residential thermal spa program to prevent work-related stress/burnout on stress biomarkers: the ThermStress proof of concept study. Issue 10 (October 2019) - Dutheil, Frédéric; Chaplais, Elodie; Vilmant, Audrey; Lanoir, Denise; Courteix, Daniel; Duche, Pascale; Abergel, Armand; Pfabigan, Daniela M.; Han, Shihui; Mondillon, Laurie; Vallet, Guillaume T.; Mermillod, Martial; et al.
Objective: Work-related stress is a public health issue. Stress has multiple physical and psychological consequences, the most serious of which are increased mortality and cardiovascular morbidity. The ThermStress protocol was designed to offer a short residential thermal spa program for work-related stress prevention that is compatible with a professional context. Methods: Participants will be 56 male and female workers aged 18 years or above. All participants will undergo a 6-day residential spa program comprising psychological intervention, physical activity, thermal spa treatment, health education, eating disorder therapy and a follow-up. On six occasions, participants' heart rate variability, cardiac remodelling and function, electrodermal activity, blood markers, anthropometry and body composition, psychology and quality of life will be measured using questionnaires and bone parameters. Results: This study protocol reports the planned and ongoing research for this intervention. Discussion: The ThermStress protocol has been approved by an institutional ethics committee (ANSM: 2016 A02082 49). It is expected that this proof of concept study will highlight the effect of a short-term specific residential thermal spa program on the prevention of occupational burnout and work-related stress. The findings will be disseminated at several research conferences and in published articles in peer-reviewed journals. Trial Registration: ClinicalTrials.gov( NCT 03536624, 24/05/2018)